Which Learning Tools Accompanying the Paid Online Version of LDOCE Do Advanced Learners of English Find Useful? - Ptasznik, Bartosz; Lew, Robert (Lexikos, 2018)
The aim of the report is twofold: to (1) briefly describe the learning tools of the Longman Dictionary of Contemporary English (LDOCE6) which are available to English learners in the paid online version of the dictionary (sixth edition); and (2) present the results of the questionnaire that was conducted on 114 students of English at the University of Warmia and Mazury in Olsztyn. The participants completed a questionnaire in which they were asked to assess the usefulness of the learning tools of the paid online version of LDOCE6. The first section of the paper introduces the reader to the five major British monolingual learners' dictionaries on the market and the most prominent features of LDOCE. The second section is a description of the learning tools available to learners of English in the paid online version of LDOCE6. The following section elaborates on the earliest questionnaire studies conducted in the field of dictionary use, and some of the problematic aspects of this research method are discussed. The report ends with a presentation of the results of the questionnaire and a brief discussion.